2021
DOI: 10.1371/journal.pone.0250933
|View full text |Cite|
|
Sign up to set email alerts
|

Potential value of urine lateral-flow lipoarabinomannan (LAM) test for diagnosing tuberculosis among severely acute malnourished children

Abstract: Background Tuberculosis (TB) is a serious co-morbidity among children with severe acute malnutrition (SAM) and TB diagnosis remains particularly challenging in the very young. We explored whether, in a low HIV-prevalence setting, the detection of mycobacterial lipoarabinomannan (LAM) antigen in urine may assist TB diagnosis in SAM children, a pediatric population currently not included in LAM-testing recommendations. To that end, we assessed LAM test-positivity among SAM children with and without signs or symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Two studies were excluded based on review of their titles and abstracts, and one study was excluded after a full-text review. Eleven studies met the inclusion criteria, and were included in this systematic review and meta-analysis ( Blok et al., 2014 ; Nicol et al., 2014 , 2021 ; Kroidl et al., 2015 ; LaCourse et al., 2018 ; Gautam et al., 2019 ; Nkereuwem et al., 2020 ; Comella-Del-Barrio et al., 2021 ; Dulce-Vasco et al., 2021 ; Schramm et al., 2021 ; Orikiriza et al., 2021 ) ( Figure 1 ). All included studies had high-quality assessment scores based on the JBI assessment checklist for diagnostic test accuracy (Table S3, see online supplementary material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded based on review of their titles and abstracts, and one study was excluded after a full-text review. Eleven studies met the inclusion criteria, and were included in this systematic review and meta-analysis ( Blok et al., 2014 ; Nicol et al., 2014 , 2021 ; Kroidl et al., 2015 ; LaCourse et al., 2018 ; Gautam et al., 2019 ; Nkereuwem et al., 2020 ; Comella-Del-Barrio et al., 2021 ; Dulce-Vasco et al., 2021 ; Schramm et al., 2021 ; Orikiriza et al., 2021 ) ( Figure 1 ). All included studies had high-quality assessment scores based on the JBI assessment checklist for diagnostic test accuracy (Table S3, see online supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…From the 11 studies included in this systematic review and meta-analysis, two were prospective observational studies ( Nicol et al., 2014 ; Kroidl et al., 2015 ), eight were cross-sectional studies ( Blok et al., 2014 ; LaCourse et al., 2018 ; Gautam et al., 2019 ; Nkereuwem et al., 2020 ; Dulce-Vasco et al., 2021 ; Nicol et al., 2021 ; Orikiriza et al., 2021 ; Schramm et al., 2021 ) and one was a retrospective study ( Comella-Del-Barrio et al., 2021 ). Among them, one study reported the diagnostic value of the Fuji LAM test in children with presumptive TB, while five studies reported the diagnostic value of the Alere LAM test and two studies reported the diagnostic value of both the Alere LAM test and the Fuji LAM test.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, we also used it for screening and diagnosis of all children <5 years of age irrespective of HIV status. This is because <5 children have a high risk of disseminated TB [ 50 , 51 ], one of the pathways through which LAM can be found in urine [ 52 ], and is further supported by data suggesting potential utility for LAM testing in HIV negative children <5 years old [ 23 , 24 ]. However, additional studies are required to determine the sensitivity and specificity of LAM in this patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Sputum or gastric aspirates were collected from all presumptive TB patients and these samples were subjected to microbiological testing for TB using Xpert MTB/RIF Ultra. The TB Lipoarabinomannan (LAM) rapid urine assay (Abott, Palantine, Illinois) was utilized if presumptive TB patients were either (a) HIV positive (regardless of CD4 count or WHO clinical staging), in line with the WHO recommendations on the use of LAM among symptomatic individuals [ 22 ], or (b) if the patient was <5 years of age irrespective of HIV status, based on evidence suggesting the incremental value of LAM testing in HIV negative children <5 years old [ 23 , 24 ]. All respiratory and urine samples were processed and examined by the clinical laboratories based at the intervention sites in accordance with national standard operating procedures for Xpert MTB/RIF Ultra and urine LAM, respectively…”
Section: Methodsmentioning
confidence: 99%
“…In children with SAM who are hospitalised, more intensive microbiological sampling and testing for potential underlying TB are needed. In children with SAM or HIV, LAM assays should be part of the diagnostic package despite their limited sensitivity, as they are more likely to detect disseminated forms of TB that are more frequent in these vulnerable groups [42,[74][75][76].…”
Section: Specific Tb Diagnostic Needs In Vulnerable Population Groupsmentioning
confidence: 99%